O pedágio e a sua natureza jurídica - Araújo, Vitor Carvalho Curvina Costa de (2014)
Turnpikes are one of the oldest ways to collect money. The charge for using roads brings us to ancient times – Mesopotamia, Roman Empire, Middle Age. After several centuries, tolls are still used and the research about its legal nature in the Brazilian current legal system shows different results. Some scholars argue that tolls are fees, but there’s another group who thinks they are fares. This article intends to analyze the concepts of tax, fee and fare, according to the national doctrine and the Supremo Tribunal Federal’s judge-made law, in order to finally ascertain which of the possible tax type belongs the toll. This discussion is based on the great difference between the legal framework of each tax type.